Improving the Welfare of a Zoo-Housed Male Drill (Mandrillus leucophaeus poensis) Aggressive Toward Visitors. Issue 4 (1st October 2016) - Martín, Olga; Vinyoles, Dolors; García-Galea, Eduardo; Maté, Carmen
Abstract : Improving the welfare of nonhuman animals in captivity and maintaining behavioral competence for future conservation purposes is of the highest priority for zoos. The behavior of an aggressive male drill ( Mandrillus leucophaeus poensis ) was assessed in Barcelona Zoo. The 2-year study presented in this article examined the effects of introducing changes in the exhibit of the drill to improve his welfare by analyzing scan behaviors. First, a partial visual barrier was applied and proved to be insufficient to decrease the long-term stress indicators assessed. Next, a feeding enrichment program was implemented. The results supported the hypothesis that feeding and explorative activities would increase, whereas apathetic and stereotypic behaviors would decrease. However, visitor-directed aggression did not vary, indicating that more profound structural modifications were needed to reduce the negative impact of the agonistic interactions between the drill and the public. The study emphasized the usefulness of environmental enrichment evaluations in assessing captive animal welfare.